Necessary Condition for an Euler-Lagrange Equation on Time Scales - Monika Dryl; Delfim F. M. Torres (Abstract and Applied Analysis)
We prove a necessary condition for a dynamic integrodifferential equation to be an Euler-Lagrange equation. New and interesting results for the discrete and quantum calculus are obtained as particular cases. An example of a second order dynamic equation, which is not an Euler-Lagrange equation on an arbitrary time scale, is given.